Genome-wide study investigating effector genes and polygenic prediction for kidney function in persons with ancestry from Africa and the Americas - Odessica Hughes; Amy R. Bentley; Charles E. Breeze; Francois Aguet; Xiaoguang Xu; Girish Nadkarni; Quan Sun; Bridget M. Lin; Thomas Gilliland; Mariah C. Meyer; Jiawen Du; Laura M. Raffield; et al. (Cell Genomics, 2024)
Summary: Chronic kidney disease is a leading cause of death and disability globally and impacts individuals of African ancestry (AFR) or with ancestry in the Americas (AMS) who are under-represented in genome-wide association studies (GWASs) of kidney function. To address this bias, we conducted a large meta-analysis of GWASs of estimated glomerular filtration rate (eGFR) in 145,732 AFR and AMS individuals. We identified 41 loci at genome-wide significance (p < 5 × 10−8), of which two have not been previously reported in any ancestry group. We integrated fine-mapped loci with epigenomic and transcriptomic resources to highlight potential effector genes relevant to kidney physiology and disease, and reveal key regulatory elements and pathways involved in renal function and development. We demonstrate the varying but increased predictive power offered by a multi-ancestry polygenic score for eGFR and highlight the importance of population diversity in GWASs and multi-omics resources to enhance opportunities for clinical translation for all.